H3.3-K27M drives neural stem cell-specific gliomagenesis in a human iPSC-derived model - Haag, Daniel; Mack, Norman; Benites Goncalves da Silva, Patricia; Statz, Britta; Clark, Jessica; Tanabe, Koji; Sharma, Tanvi; Jäger, Natalie; Jones, David T. W.; Kawauchi, Daisuke; Wernig, Marius; Pfister, Stefan (Cancer cell, 2021)
Diffuse intrinsic pontine glioma (DIPG) is an aggressive childhood tumor of the brainstem with currently no curative treatment available. The vast majority of DIPGs carry a histone H3 mutation leading to a lysine 27-to-methionine exchange (H3K27M). We engineered human induced pluripotent stem cells (iPSCs) to carry an inducible H3.3-K27M allele in the endogenous locus and studied the effects of the mutation in different disease-relevant neural cell types. H3.3-K27M upregulated bivalent promoter-associated developmental genes, producing diverse outcomes in different cell types. While being fatal for iPSCs, H3.3-K27M increased proliferation in neural stem cells (NSCs) and to a lesser extent in oligodendrocyte progenitor cells (OPCs). Only NSCs gave rise to tumors upon induction of H3.3-K27M and TP53 inactivation in an orthotopic xenograft model recapitulating human DIPGs. In NSCs, H3.3-K27M leads to maintained expression of stemness and proliferative genes and a premature activation of OPC programs that together may cause tumor initiation.
Gesehen am 05.02.2021